The education of resettled young Syrian refugees in England and the figured world of mobility - Fakoush, Haya (2024)
Refugee education has yet to provide adequate provisions for quality education for refugees. This thesis seeks to highlight the lived experiences of young, resettled refugees to challenge the taken for granted assumptions on refugee youth. Drawing on a longitudinal qualitative study with young people resettled via the Syrian Vulnerable Persons Resettlement Scheme (VPRS), this study shows how they engage with the sociocultural constructs in education and their communities. Using the figured worlds theory (Holland et al, 1998), the research examines the identity production of resettled, young Syrians in England within the figured world of mobility, relying on the mobility approach (Nail, 2015) to understand their migration journey and its influence on their identity and education. As young Syrians are forced to migrate, they soon recognise the privilege of the non-mobile and the ‘burden’ bestowed upon them. The term ‘burdened mobility’ is introduced to represent the un-privilege of the mobile population. This research also portrays the capacity of young people to create avenues of change by figuring their desired position to re-imagine their future self amid the altered physical and emotional spaces. The findings discuss the living spaces of the young people pre- and post-resettlement, the significance of social connections and the diverse scope of their educational experiences. It dives into their stories to uncover legal artefacts of the refugee status, the home as family artefact, food as hospitality artefact to nurture social bonds. The research provides thought-provoking revelations on challenging our assumptions that are conditioned by non-mobility for what is deemed ordinary and how we foster and sustain belonging. This thesis also advocates for youths’ education to be unbound by schools harnessing the collective capacities within communities to imagine an education that traverse the physical space and standardised notion of measuring in education. In discussing the implication of the research, the thesis advocates for establishing a network for reciprocity for those engaging in research with forced migrants. This is a necessity as the power imbalance continues to grow between researchers and those involved in the research particularly in the field of forced migration.